Combinatory antitumor therapy by cascade targeting of a single drug - Aiyun Liu; Huaisong Wang; Xiaoshuang Hou; Yu Ma; Gongjun Yang; Yanglong Hou; Ya Ding (Elsevier, 2020)
Combination therapy has shown its promise in the clinic for enhancing the efficacy of tumor treatment. However, the dose control of multiple drugs and their non-overlapping toxicity from different drugs are still great challenge. In this work, a single model drug, paclitaxel (PTX), is used to realize combination therapy and solve the problems mentioned above. Either PTX or its triphenylphosphine derivative (TPTX) is encapsulated in galactose-modified liposomes (GLips) to obtain GLips-P or GLips-TP, which are simply mixed in different ratios to finely control the proportion of PTX and TPTX. These mixed liposomes, GLips-P/TP, feature a cascade target delivery of PTX, from tissue to cell, and then to organelle. PTX plays a primary role to cause the cytotoxicity by microtubule bindings in cytoplasm, while TPTX is proved to increase the intracellular levels of caspase-3 and caspase-9 that cause apoptosis via a mitochondria-mediated pathway. Notably, GLips-P/TP 3:1 exhibited the significant drug synergy in both cytotoxicity assay of HepG2 cells and the treatment efficacy in Heps xenograft ICR mouse models. This work not only demonstrates the great promise of a cascade targeting delivery for precise tumor treatment, but also offers a novel platform to design combinatory therapy systems using a single drug. KEY WORDS: Combin chemotherapy, Single drug, Paclitaxel, Microtubules, Mitochondria, Cytotoxicity